Austerity Urbanism: From Redistributive transfers to debt based finance - Jorge Afonso (U.Porto Journal of Engineering)
Austerity urbanism is an explanatory concept that alerts planners, politicians and society. The tripartite explanation of the concept of Austerity: as a result, solution, or even as a cause is part of the knowledge of this research article. Austerity embedded in the political choices of neoliberalism. Austerity rooted in the liberal thinking. Austerity Urbanism intertwined with: destructive creativity, deficit politics and devolved risk. After years of Austerity (Urbanism), governments are still ill-prepared to deal with the current urban crisis. New democratic instruments are needed to regain control over capital and to reform, modernize economic and social redistributive efficiency and effectiveness.